2006
DOI: 10.1074/mcp.m600118-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PSME3 as a Novel Serum Tumor Marker for Colorectal Cancer by Combining Two-dimensional Polyacrylamide Gel Electrophoresis with a Strictly Mass Spectrometry-based Approach for Data Analysis

Abstract: The purpose of this study was to identify and validate novel serological protein biomarkers of human colorectal cancer (CRC).The PSME3-containing spot on tumor gels showed no visible difference to the corresponding spot on matched control gels. MS analysis revealed the presence of two proteins, PSME3 and annexin 4 (ANXA4) in one and the same spot on tumor gels, whereas the matched spot contained only one protein, ANXA4, on control gels. Therefore, dysregulation of PSME3 was masked by ANXA4 and could only be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 41 publications
4
107
0
1
Order By: Relevance
“…Increasing evidence has also suggested that overexpressed REGγ could positively contribute to cell cycle progression in the development of various human cancers. For instance, REGγ has been reported to be highly expressed in thyroid cancer (Okamura et al, 2003) and in colorectal cancer serum (Roessler et al, 2006). Recently, the overexpressed REGγ has been also found in human breast cancer cells and the metastatic lymph nodes (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has also suggested that overexpressed REGγ could positively contribute to cell cycle progression in the development of various human cancers. For instance, REGγ has been reported to be highly expressed in thyroid cancer (Okamura et al, 2003) and in colorectal cancer serum (Roessler et al, 2006). Recently, the overexpressed REGγ has been also found in human breast cancer cells and the metastatic lymph nodes (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…troponin) at the proteomics scale, and traces back to the protohistory of proteomics 25 . The comparison between differently diseased versions of the same tissue or cell type has received brilliant recent demonstration on the search for a metastatic power associated biomarker 26 . It can be argued that such a comparison has been carried out many times, with limited success.…”
Section: A Relevant Questionmentioning
confidence: 99%
“…More recently, REGγ was known to regulate p53 stability/activity in an Mdm2-dependent manner in vitro (11,12). Overexpression of REGγ has been linked to progression of some cancers (18,19). REGγ-dependent regulation of p53 prompted us to investigate whether REGγ −/− mice may display premature aging.…”
mentioning
confidence: 99%